Monetary Transmission and Financial Market Stability in Indonesia: Evidence from Yield Curve Dynamics and Implications for Islamic Finance - Palupi Pratiwi; Ahmad Habibi; Muhammad Iqbal Fasa (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to apply the Christensen, Diebold, and Rudebusch (CDR) model to analyze monetary transmission through the government bond yield curve in Indonesia from 2010 to 2024. It specifically seeks to extract the latent factors (level, slope, curvature) of the yield curve and assess their interaction with key macroeconomic variables, namely inflation and GDP. The research employs a two-stage methodology: first, estimating the latent factors using the Arbitrage-Free Nelson-Siegel (AFNS) model within a state-space framework; and second, analyzing the dynamic relationships using a Vector Autoregression (VAR) approach complemented by Impulse Response Functions (IRF) and Forecast Error Variance Decomposition (FEVD). The results confirm the applicability of the CDR model, revealing a dominant level factor linked to inflation expectations, a consistently negative but flattening slope factor indicating moderate growth expectations, and a highly volatile curvature factor. The conclusion is that monetary policy transmission is effective in the short term but weaker over the long term. The study recommends future research to incorporate machine learning techniques and high-frequency data to better capture non-linearities and structural breaks in the post-pandemic economic environment